Synthesis and structural studies of covalent organic frameworks prepared from polyhedral oligosilsesquioxane for naproxen adsorption - Bala, Suleiman (2022)
Covalent organic frameworks (COFs) are porous crystalline materials made up of organic components joined by strong reversible covalent bonds that have a persistent influence on the geometry and permeability of the arrangement. These substances are totally composed of light components such as H, B, C, N, O, and Si. Pharmaceuticals and personal care products (PPCPs) are an emerging problem as environmental contaminants. An "emerging toxin" such as naproxen which a nonsteroidal antiinflammatory drug, is a toxic compound that has conquered or is manufactured in significant quantities in an ecosystem, causing some persistence and harm to living species. Hence, the development of polyhedral oligomeric silesquioxane (POSS) COFs as adsorbents for the removal of naproxen is crucial. POSS octa(phenyl) silesquioxane (OPS) was nitrated to produce octa(nitrophenyl) silesquioxane, which was then reduced to yield octa(aminophenyl)silesquioxane (OAPS). Four newly POSS COFs with various linkers, namely, COF-S4, OAPS with 1,5-dihydroxyanthraquionone (1,5-DHAQ, L1); COF-S7, OAPS with 2-methylanthraquionone (2-MeAQ, L2); COF-S12, OAPS with Terephthalaldehyde (TPA, L3); COF-S14, OAPS with 1,8-dihydroxyanthraquionone (1,8-DHAQ. L4) were successfully synthesised by solvothermal condensation method using Schiff base reaction (R₁R₂C=NR'), with a molar ratio 1:8 for OAPS to linker (L1, L2, L3 and L4), at temperature 120, 125, 100 and 120°C for COF-S4, COF-S7, COF-S12 and COF-S14 respectively. The nanomaterials obtained were investigated using numerous spectroscopy techniques. The formation of large crystal lattice unit cells of the COFs frameworks was indicated by the peaks observed at low angles of less than 10°. The functional groups were investigated by FTIR which exhibited that the formation of the frameworks was attained through the Schiff base formation (C=N). Similarly, the Si−O−Si bonds for the synthesised COFs were all shown, which further proved that the materials were formed. 13C and 28Si CP-MAS NMR analysis confirmed the formation of the COFs through the C=O peaks in the range 180-200 ppm for the linkers and the existence of the C=N peaks in the range of 160-180 ppm for the nanomaterials produced. 28Si NMR further affirmed the retention of silicone in the compounds after the synthesis. The COFs displayed excellent thermal durability for up to 400°C for COF-S4 and COF S14, and 600°C for COF-S7 and COF-S12, respectively. The structural morphology FESEM of the compounds obtained displayed that the materials were nano crystals with nano-grain size pores and demonstrated the presence of all the expected elemental composition via EDX analysis. N2 physisorption (BET) analysis demonstrated that the materials showed Type IV isotherm, and H3 hysteresis loop, which is a characteristic of mesoporous material. The remedied effluent was investigated, and a significant performance was recorded in the removal capability of the naproxen over COF-S4, COFS7, COF-S12, and COF-S14 as 76%, 70%, 86% and 77% at a contact time of 210, 210, 270, and 270 min, respectively, at a constant dose of 0.05 g and pH 7. The maximum adsorption capabilities of the compounds were found to be 37, 35, 42, and 38 mg/g. The pH effect signifies that there is steady exclusion with a rise in pH to 9. At pH 9, the drop value was achieved for all COFs except for COF-S12 which was observed at pH 11, owing to the further negative charge, consequential to the repulsion between the synthesised COFs and naproxen solution. Investigation of the as-synthesised materials demonstrated admirable performance in reusability in the adsorption removal of naproxen. The as-synthesised COFs are envisioned as future adsorbents for removing anti-inflammatory drugs (AIDs) from water due to their ease of production, notable adsorption effectiveness, and admirable reusability.